Glucagon-like peptide-1 receptor-agonists treatment for cardio-metabolic parameters in schizophrenia patients: a systematic review and meta-analysis - Khaity, Abdulrhman; Mostafa Al-dardery, Nada; Albakri, Khaled; Abdelwahab, Omar A.; Hefnawy, Mahmoud Tarek; Yousef, Yaman A. S.; Taha, Ruaa E.; Swed, Sarya; Hafez, Wael; Hurlemann, Rene; Elsayed, Mohamed E. G. (Frontiers in Psychiatry, 2023)
Aims We performed this meta-analysis to evaluate the efficacy and safety of glucagon-like peptide-1 receptor-agonists (GLP-1RA) treatment on cardio-metabolic parameters among antipsychotic-treated patients with schizophrenia. Methods We searched the Web of Science, Cochrane Central Register of Controlled Trials, PubMed, PsycINFO, and Scopus for relevant Randomized Clinical trials (RCTs) from inception until 1 August 2022. Documents were screened for qualified articles, and all concerned outcomes were pooled as risk ratios (RR) or mean difference (MD) in the meta-analysis models using Review Manager (RevMan version 5.4). Results Pooling data from 7 RCTs (398 patients) showed that GLP-1 RA was superior to placebo with regard to body weight [MD = - 4.68, 95% CI (-4.90,−4.46), P < 0.00001], waist circumference [MD = - 3.66, 95% CI (-3.89,−3.44), P < 0.00001], body mass index (BMI) [MD = - 1.09, 95% CI (-1.25,−0.93), P < 0.00001], systolic blood pressure (SBP) [MD = - 3.07, 95% CI (-3.61,−2.53), P < 0.00001], and diastolic blood pressure (DBP) [MD = - 2.02, 95% CI (-2.42,−1.62), P < 0.00001]. The total effect did not favor either of the two groups with respect to insulin and respiratory adverse events [MD = - 0.06, 95% CI (-0.36, 0.24), p = 0.70], [RR = 0.66, 95% CI (0.31, 1.40), p = 0.28]; respectively. Conclusion Our analysis revealed that GLP-1 RA treatment is safe and effective on cardio-metabolic parameters over control in antipsychotic-treated patients with schizophrenia. Nevertheless, the present evidence is not sufficient to confirm the safety and efficacy of GLP-1RA treatment on insulin and respiratory adverse events. Therefore, further studies are recommended. Systematic review registration http://www.crd.york.ac.uk/PROSPERO/, identifier: CRD42022333040.